2019
DOI: 10.3389/fpsyg.2019.01739
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being From a Just-World Perspective: A Multi-Dimensional Approach in a Student Sample

Abstract: In a cross-sectional study with N = 627 individuals ( M age = 22.8, SD age = 7.3, 147 males, 480 females, 106 non-religious, 456 religious), we investigated personal belief in a just world (BJW) as a resource for undergraduates’ subjective well-being and expected a positive relation between both constructs due to recent studies. We not only aimed at replicating but also extending recent findings by investigating a Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 84 publications
3
8
0
1
Order By: Relevance
“…Conversely, the stronger correlation of GBJW, compared to PBJW, with religiosity implies that religion may be more involved with the aspects of justice in society and for people in general. In addition to replicating previous research on BJW correlates (Bègue, 2002;Donat et al, 2016;Nartova-Bochaver et al, 2019), these finding support the different psychological functioning of GBJW and PBJW.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Conversely, the stronger correlation of GBJW, compared to PBJW, with religiosity implies that religion may be more involved with the aspects of justice in society and for people in general. In addition to replicating previous research on BJW correlates (Bègue, 2002;Donat et al, 2016;Nartova-Bochaver et al, 2019), these finding support the different psychological functioning of GBJW and PBJW.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, previous research on BJW's effects on well-being suggests that both GBJW and PBJW are associated with self-esteem (i.e. high self-esteem reflects a primary feeling of self-worth and self-admiration, while low self-esteem represents unhappiness with oneself, self-denial, and lack of self-respect), life satisfaction, and other components of well-being (Donat et al, 2016;Nartova-Bochaver et al, 2019;Tatsi & Panagiotopoulou, 2021). Also, the literature emphasizes that PBJW is a stronger predictor of these constructs.…”
Section: Bjw and Well-beingmentioning
confidence: 99%
“…Since interactions between religious strain and different dimensions of well-being are somewhat complex and are frequently influenced by "third" factors (Pargament et al 2005), we decided on a research design including self-esteem as an underlying psychological mechanism of this relationship. The choice was dictated by the fact that self-esteem, conceptualized as an individual overall evaluation and respect of the self (Rosenberg 1965), can act as a buffer against adverse experience, and decrease the influence of negative life events (Mann et al 2004;Nartova-Bochaver et al 2019). Indeed, Pearlin and Schooler (1978) considered self-esteem to be one of the features of personality that people use to help themselves endure dangers posed by events and conditions in their environment.…”
Section: Religious Struggle Life Satisfaction and Self-esteemmentioning
confidence: 99%
“…According to the results, there was a positive and significant path coefficient between BJW and spiritual well-being with negative affect, and an insignificant indirect path coefficient between the two aforesaid variables with positive affect. Accordingly, it was concluded that the negative affect had a positive and significant effect on the relationships between BJW and spiritual well-being (16). Thus, when facing accidents or unfair and unjust events, the individuals will have strong BJW and experience negative affect and even though at first they might get angry, they will become relaxed at the end as they believe that the world will do them justice.…”
Section: Discussionmentioning
confidence: 99%